2008
DOI: 10.1007/s11277-008-9646-3
|View full text |Cite
|
Sign up to set email alerts
|

A Simple 3-D Geometric Channel Model for Macrocell Mobile Communications

Abstract: One of the fundamental research areas in wireless communications is the development of realistic models that can efficiently and accurately describe the wireless propagation channel. Most of the proposed models disregard the three dimensional character of the signal spread or use techniques with excessive computational complexity. In this paper, we develop a simple 3-D geometric scattering model for the uplink of a macrocell mobile environment that provides the statistics of Angle-of-Arrival (AoA) of the multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 38 publications
(69 reference statements)
0
47
0
Order By: Relevance
“…In this case, it is also α R 1 ,R 2 = kα R 1 ,R 2 due to (10). In the single disk scenario [2], simulations have shown that (11) gives adequate results for R 1,2 = Rα 2 1,1 4 and D = α R,R /2 (R is the disk radius).…”
Section: The Nodal Distance Distribution Modelmentioning
confidence: 97%
See 1 more Smart Citation
“…In this case, it is also α R 1 ,R 2 = kα R 1 ,R 2 due to (10). In the single disk scenario [2], simulations have shown that (11) gives adequate results for R 1,2 = Rα 2 1,1 4 and D = α R,R /2 (R is the disk radius).…”
Section: The Nodal Distance Distribution Modelmentioning
confidence: 97%
“…In our analysis, we develop a geometrical-based method [8][9][10][11][12][13][14][15] and provide simple integral expressions for the cumulative distribution function (cdf) of the distance between nodes that are uniformly located within circular-shaped networks. To the best of the author's knowledge, computation of distance distribution includes awkward expressions and requires time-consuming calculations [5].…”
Section: Introductionmentioning
confidence: 99%
“…We present three 2-D geometrical-based models for the description of the probability of uplink interference that assume circular and hexagonal cells. At this point, we have to notice that two-dimensional modeling is adequate for the description of the azimuth angular spreading of the propagating signals but fails to describe any signal variations in the elevation plane (Fuhl et al, 1997;Kuchar et al, 2000;Baltzis & Sahalos, 2009a, b;Nawaz et al, 2010). In the development of the models, certain assumptions have been made.…”
Section: The Impact Of the Shape Of The Cells On Co-channel Interferementioning
confidence: 99%
“…However, the signals reflected from rooftop and high-rise buildings raise the importance of the inclusion of an elevation plane in the mobile [15]. Therefore, it is very essential to consider the spreading of multipath signals in 3-D space (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is very essential to consider the spreading of multipath signals in 3-D space (i.e. simultaneously both in azimuth and elevation planes) [15][16][17][18][19][20][21][22]. In [16,17], power spectral density and PDFs of AOA for a nonzero elevation plane using a 3-D scattering model are theoretically derived, and in these models authors do not consider spreading of multipath waves in the azimuth and elevation planes.…”
Section: Introductionmentioning
confidence: 99%